Pelatihan untuk Meningkatkan Pemahaman Guru SMP N 2 Gubug dalam Penulisan Artikel Ilmiah di Jurnal Nasional - Nizaruddin, Nizaruddin; Muhtarom, Muhtarom; Nugraha, Aryan Eka Prasetya; Murtianto, Yanuar Hery; Nuvitalia, Duwi; Zuhri, Muhammad Saifuddin (Perkumpulan Kualitama Edukatika Indonesia, 2022)
Many teachers have difficulties in publishing scientific articles in National Journals. This service activity aims to provide training and assistance to teachers at SMP N 2 Gubug so that they have the knowledge and skills in making scientific articles and can be published in National Journals. The method used to achieve this goal is to train more questions and answers and practice as well as mentoring. The training material is presented with more practice than theory. The team's expertise is very helpful and useful in solving service partner problems so that teachers at SMP N 2 Gubug can create and publish scientific articles. Community service activities have been able to improve teacher understanding in the preparation of scientific articles, the use of Mendeley for reference management and how to submit scientific articles in national journals through OJS. This is in line with the increase in the average pre-test score from 3,494 which increased to 4,381.